Coordination‐Accelerated Radical Formation from Acyclic Enediynes for Tumor Cell Suppression. Issue 23 (28th November 2019) - Li, Baojun; Zhang, Mengsi; Lu, Haotian; Ma, Hailong; Wang, Yue; Chen, Huimin; Ding, Yun; Hu, Aiguo
Abstract: A maleimide‐based acyclic enediyne with salicylaldiminato substituents at the alkyne termini was synthesized, which was further chelated with three kinds of metal‐ions, Cu II, Zn II, and Mg II, and form metalloenediynes. The cycloaromatization of this thermally inactive enediyne ligand was greatly accelerated through the coordination with metal ions. Specifically, the Cu II ‐metalloenediyne showed an extremely low onset temperature of 55 °C and underwent spontaneous cycloaromatization at ambient temperature to produce free radicals, followed by generation of reactive oxygen species in the physiological environment. The metalloenediyne exhibited excellent DNA cleavage ability and high cytotoxicity towards HeLa cells, with half‐maximal inhibitory concentration values comparable to many commercial antitumor agents. The combination of the electron‐withdrawing effect of the maleimide moiety at the ene position and metal coordination at the yne termini provides a new inspiration for designing and synthesizing highly efficient enediyne antitumor agents. Abstract : An acyclic enediyne functions via coordination‐accelerated radicals to induce ROS and DNA cleavage, thereby inhibiting cancer cell growth.